Non-communicable diseases risk factors among government school teachers in Jodhpur, Rajasthan - Vibha Joshi; Nitin Kumar Joshi; Praveen Suthar; Yogesh Kumar Jain (Intelektual Pustaka Media Utama, 2021)
Non-communicable diseases (NCDs) are considered as life-style diseases. School teachers' behavior in this context could be transmitted to students that may act as determining factor of prevention for NCDs at primordial level. Aim of this study is to assess the prevalence of risk factors among teachers and their practices with respect to common NCDs. A cross-sectional study was conducted in Jodhpur among 394 government school teachers. Questionnaire was adopted from WHO STEPS tool and responses were documented which included socio-demographic details, anthropometric measurements and risk factors including diet, hours of physical activity, smoking and alcohol intake. Mean age of participants was 43 years out of which 23% were found to be having blood pressure more than 140/90 mm of Hg at the time of interview. 4.8% consumed alcohol and 1.5% was smokers. Mean body mass index (BMI) was found to be 25.4 while only 13% had their cholesterol checked post 35 years of age. The 23.6% had knowledge of reducing fat by using the right type of cooking oil, 35.7% were engaged in any daily physical activity and 76% knew that excess salt was not good for health. This survey assessed baseline levels by identifying the overall prevalence and associated risk factors that provided first step towards initiating surveillance for NCDs among school teachers in Jodhpur, Rajasthan, whilst delivering the necessary information concerning with developing a suitable framework for determining priorities over intervention.